Banking sector liberalization and the impact of foreign banks: The case of Russia - Andrei Vernikov (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
The paper aims to make the first assessment of the impact that presence of foreigncontrolled banks have produced on the Russian economy and banking system. So far foreign banks have gained a modest market share in Russia with 7% of the combined assets of the banking system. They have made some contribution to the improvement of financial intermediation, especially in terms of reallocation of savings towards Russian corporate borrowers. The presence of foreign banks has rendered some additional resilience to the Russian banking system during and after the financial crisis of 1998. Evidence from Russia, however, supports only some of the presumed benefits from foreign bank participation in transition economies. Insufficient proof was found to confirm assumptions that foreign banks: lend more actively, cheaper or for longer tenors than local peers; sufficiently support the local banking system during liquidity crises; enhance positive structural changes in the host economy; catalyze foreign direct investment; or disseminate product knowledge and new banking technologies.
Keywords: 330; Internationale Bank; Bankenregulierung; Russland